(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Rasapushpa, an Ayurvedic mercurial preparation, is a very potent formulation due to its therapeutic properties but carries potential risks due to the presence of mercury. The acute toxicity of Rasapushpa, prepared by two distinct methods- the classical Valukayantra method (RPVY) and the conventional Electric Muffle Furnace method (RPEMF)- was assessed in Wistar rats. Using the OECD Test Guideline 423, the study determined the lethal dose (LD50) and observed any clinical signs of toxicity following oral administration. Objectives: To evaluate the Acute toxicity study of Rasapushpa prepared by both methods. Materials and Methods: This comparative Acute toxicity study was conducted at the Ribosome Research Centre, Kudsad, Surat, using two samples of Rasapushpa: RPVY (classical method) and RPEMF (conventional method). By adopting OECD Test Guideline 423. Discussion: Rasapushpa prepared by Valukayantra (RPVY) exhibited LD50 at 300mg/kg body weight, while Rasapushpa prepared by Electric Muffle Furnace (RPEMF) showed LD50 higher than 2000 mg/kg. Conclusion: After human dose conversion, both samples were found safe in the dose range given by Rasatarangini for Rasapushpa (62.5 to 312.5 mg).